Robbing the Jews : the confiscation of Jewish property in the Holocaust, 1933 - 1945 - Dean, Martin 1962- (Cambridge Univ. Press, 2010)
The Nazis' initial confiscation measures -- Mounting obstacles to Jewish emigration, 1933--1939 -- The Anschluss and Kristallnacht: accelerating aryanization and confiscation in Austria and Germany, 1938--1939 -- Blocking Jewish accounts and preparations for mass confiscation, 1939--1941 -- Destruction and plunder in the occupied East: Poland, the Soviet Union, and Serbia -- Settling accounts in the wake of the deportations -- Plunder by decree: the confiscation of Jewish property in German-occupied Western Europe -- Sovereign imitations: confiscations by states allied to Nazi Germany -- Receiving stolen property: neutral states and private companies -- Seizure of property and the social dynamics of the Holocaust